Network evolution in theory and as observed, the case of the Industrial Knowledge Bank of Latin America. - Baquero Cruz, Gesny Yadira; Florez Torres, Greys M.; Hanappi, Gerhard (TECCIENCIA, 2022)
This paper provides an evaluation of a theoretical approach of network theory that describes network evolution by comparing it to an ob- served evolution of an industrial cooperation network connecting different countries. The theoretical approach considered is the well-known preferen- tial attachment mechanism leading to power-law distributions developed by Albert Barabási. The empirical phenomenon studied is the evolution of the Industrial Knowledge Bank (IKB) maintained by The United Nations Indus- trial Development Organization (UNIDO). By fitting a discrete power law to the empirical data collected during the 4 years of operation of the IKB project and testing the goodness-of-fit using the bootstrapping procedure, it is shown that the theoretical framework in its most elementary form is adequate to grasp the essential features of the observed case. The compari- son also leads to an improved understanding of very influential social factors like language and geographical distance, thus can give valuable insight for the further theoretical advances in theoretical work on network evolution and its applications to Social, Industrial, and Economic Development.